FUNCTIONAL STATE OF THE MICROCIRCULATION OF THE SKIN ACCORDING TO LASER DOPPLER FLOWMETRY IN PATIENTS WITH ATRIAL FIBRILLATION WHO UNDERWENT CARDIOEMBOLIC STROKE - I. A. Zolotovskaya; I. L. Davydkin; A. A. Fedorovich; O. M. Drapkina (Столичная издательская компания, 2017)
Aim. To evaluate the features of blood flow at the level of the microcirculatory bed of the skin (MC) in the conditions of comorbid pathology and increased coagulation potential of the blood in patients with atrial fibrillation (AF).Material and methods. The following groups were formed by random sampling: the main (group 1, n=50) group of patients with paroxysmal or persistent form of AF, after cardioembolic stroke. The comparison group (group 2, n=50) consisted of patients with paroxysmal or persistent AF without a history of stroke. The control group (group 3, n=50) - patients comparable on the basic parameters of patients from groups 1 and 2, but without AF and stroke. The plasma levels of von Willebrand factor (vWF), tissue plasminogen activator inhibitor-1 (PAI-1), antithrombin III (AT III) and plasminogen were determined. All MC parameters were studied with a single-channel laser cutaneous blood flow analyzer for the general practitioner "LAKK-OP" in the area of the finger pad during the period, when a patient had sinus rhythm.Results. The obtained results indicate the disorders of microcirculation processes in patients with AF after stroke, which are expressed in decrease in tissue perfusion, specific oxygen consumption (I) and relative perfusion of the microcirculation saturation (Sm). Significantly higher levels of vWF, PAI-1 and low levels of AT III were observed in patients with AF and stroke than these in the group of patients with AF. It was found that Sm in patients of the group 1 statistically significantly correlated with vWF (r=-0.61; p=0.0032), plasminogen (r=0.45; p=0.0084), PAI-1 (r=-0.43; p=0.0027) and AT III (r=0.49; p=0.0065).Conclusion. The revealed disorders of microcirculatory processes are significantly related with the disturbances of the hemostatic function of the endothelium. From the pathophysiological point of view, that is one of the negative risk factors of the development of recurrent thrombus formation.